Wenn es nicht mehr alleine geht – Inanspruchnahme ambulanter Unterstützungsangebote von Menschen mit Demenz: der Bayerische Demenz Survey (BayDem) - Karrer, Linda; Dietzel, Nikolas; Wolff, Franziska; Kratzer, André; Hess, Manuela; Grässel, Elmar; Kolominsky-Rabas, Peter (Gesundheitswesen, 2020)
Background The increasing prevalence of dementia raises challenges concerning the care of people with dementia (pwd). The care of pwd is mainly conducted by informal caregivers who are faced with several burdens; however, use of care services is generally low. The aim of this study was to identify predictors of the use of outpatient care services. Methods The Bavarian Dementia Survey (BayDem) is a multi-centre, longitudinal study that was conducted at 3 different sites in Bavaria, Germany. Participants were people with dementia (pwd) (according to ICD-10) and their informal caregivers. Data were collected by standardised face-to-face interviews using well-designed instruments in cooperation with local partners. Logistic regression analysis was carried out in order to identify predictors of the use of outpatient care services. Results In total, 364 pwd and 339 informal caregivers were included at the beginning of the study BayDem. The use of supportive care services was generally low. One-third of all participants used outpatient care services. In the logistic regression analysis, the following significant predictors for the use of outpatient care services 6 months after baseline were identified: severity of cognitive impairment of the pwd; use of outpatient care at the beginning of the study. Conclusion The low use of outpatient care services is a well-known paradoxical phenomenon. Such services can help give relief to informal caregivers. In order to enhance the use of supportive outpatient care services, there should be more focus on innovative health service delivery models with a low access threshold barrier. Besides more public campaigns, more guidance for existing offers is needed.
CRIS-Team Scopus Importer:2020-02-04
Keywords: informal caregivers; outpatient care; People with dementia; Resource Utilization in Dementia (RUD); use of care services